STRENGTH ANALYSIS OF SHIPLIFT SYSTEM COMPONENTS - Elektra Tambunan, Alvo
As an archipelagic country, the activities of most Indonesian people cannot be separated from sea transportation. The most common means of sea transportation used are ships. Along with the development of the times, ships operating in Indonesian waters are increasingly modern and sophisticated. Therefore in the process of care and maintenance should not be arbitrary. One mechanism that is often used today is the shiplift system. Shiplift system consists of several components that are combined into three subsystems. The subsystems in question are the hoist system, transfer system, and trestle. The hoist system consists of winch, pulley system and platform components and has the function of lifting the ship. Trestle is a subsystem that has a function to directly withstand the ship's load. The transfer system consists of cross beam, bogie, and rail components which function to move the ship from the platform to the ship yard to do work. In this final project, a strength analysis will be carried out on the components incorporated into the trestle and transfer system sub-systems. The analysis to be carried out is the strength analysis of the component structure using the Abaqus finite element method software. The result obtained is that the maximum stress experienced by all analyzed components, namely trestle, cross beam, bogie, and rail, is still below the yield strength limit of the material of the component. For the trestle and cross beam components, the most optimal design is selected based on weight considerations and the safety factor between the maximum stress and the yield strength of the material.